Social Work under COVID-19: A Thematic Analysis of Articles in 'SW2020 under COVID-19 Magazine'. (20th May 2021) - Sen, Robin; Kerr, Christian; MacIntyre, Gillian; Featherstone, Brid; Gupta, Anna; Quinn-Aziz, Abyd
Abstract: This article presents a thematic analysis of 100 articles which appeared in 'SW2020 under COVID-19' online magazine, authored by people with lived experience, practitioners, students and academics. The magazine was founded by an editorial collective of the authors of this article and ran as a free online magazine during the period of the first UK COVID-19 lockdown period (March–July 2020). It contained a far higher proportion of submissions from the first three groups of contributors, above, than traditional journals. The analysis is organised under four analytic themes: 'Hidden populations; Life, loss and hope; Practising differently and Policy and system change' . The article concludes by describing the apparent divergence between accounts that primarily suggest evidence of improved working relationships between social workers and those they serve via digital practices, and accounts suggesting that an increasingly authoritarian social work practice has emerged under COVID-19. We argue that, notwithstanding this divergence, an upsurge in activism within social work internationally during the pandemic provides a basis for believing that the emergence of a community-situated, socially engaged social work is possible post-pandemic. Abstract : 'SW 2020 under COVID-19' is a free online magazine. It was established as a forum for people to raise issues connected to social work and COVID-19. It ran for five editions during the first UK lockdown (from March to July 2020). In that time, it published 100 articles authored by people with lived experience, practitioners, students and academics. It contained a far higher proportion of submissions from the first three groups of contributors than traditional journals, and attracted submissions from all four countries in the UK, as well as a number of international submissions. This journal article is based on an analysis of the content of those 100 articles. The analysis provides insights into some of the key questions around policy and practice changes connected to social work during this period. These questions include: What were the key challenges for those providing and receiving social work services under COVID-19? What were the key policy and practice developments and their implications, both positive and negative? What was the experience of living, and of bereavement, during this time? And, what does the upsurge in social work activism during this time herald for social work's future?